RANCANG BANGUN WEB PORTAL SEMINAR NASIONAL IKRA-ITH VERSI 3 MENGGUNAKAN YII2 DAN REACT NATIVE - Rezky, Moch; Budilaksono, Sularso; Suwarno, Muhammad Anno (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
Seminar is an activity that aims to conduct a thorough study of a particular topic with problem solving that requires interaction between seminar participants and is assisted by professors or scholars. The problem that arises is the application of the seminar participant registration system which is still done manually or via sms or whatsapps, with a few officers. QR-Code technology is a type of matrix code or two-dimensional bar code developed by Denso Wave with the main functionality that can be easily read by a QR scanner which stands for quick response, which in accordance with its purpose is to convey information quickly and get a fast response too. System application National Seminar Ikraith version 3 is web-based and android, and can manage computerized participant registration, payment transactions and certificate data of participants. By implementing QR-Code technology, namely by implementing an e-ticketing system in seminar participant registration, participants will receive an e- ticketing containing QR-Code as entry access during the seminar after completing payment. And then after the participant will get an e-certificate after completing the seminar. Where in the e-certificate there is a QR-Code which is expected to reduce or eliminate the level of forgery of the national seminar certificate.